Peritoneal carcinomatosis of colorectal origin treated by cytoreductive surgery and hyperthermic intraoperative peritoneal chemotherapy at the Bulovka University Hospital - Bartoška, P; Antoš, F; Vobořil, R; Vítek, P; Marx, J; Holečková, P; Novotný, M; Kengbaeva, M (Rozhledy v chirurgii, 2021)
INTRODUCTION: Peritoneal carcinomatosis (PK) of colorectal origin is a malignant tumour of the peritoneum caused by spreading of colorectal carcinoma (KRK) over the peritoneal surface of the abdominal cavity and its organs. PK occurs as a synchronous tumour in 1520% of patients, and as metachronous disease in 2550% of patients. METHODS: A group of 66 patients operated on for PK was retrospectively evaluated; 18 patients were excluded due to insufficient data. We evaluated 48 patients in total (22 men and 26 women) with mean age of 58 and 53 years, respectively; 12 patients (25%) were aged over 65 years. The patients were operated on between 2000 and 2019 using the Sugarbaker´s method of maximal cytoreduction (CRS) + HIPEC (Hyperthermic Intraoperative Peritoneal Chemotherapy). We evaluated the length, median survival, the incidence of complications and lethality in relation to the Peritoneal Carcinoma Index (PCI) and the Completeness of Cytoreduction (CC) score. The patients were divided into two subgroups according to the PCI score (012 and >12, respectively) and the CC score (CC 01 and CC 23, respectively). RESULTS: The mean survival was 26.3 months in the group with PCI up to 12 and 21.4 months in patients with PCI above 12 (p=0.02). In the group with CC 01 the mean survival was 27.1 months, while in the patients with the CC 23 it reached 12.6 months (p=0.06). The morbidity rate requiring an intervention was 18.7% and the lethality rate was 6.25% in the entire group. The median survival of the entire group was 22 months (1334 months). CONCLUSION: Literary references and our results are comparable, confirming the high efficiency of this method both in our country and worldwide. The use of CRS and HIPEC, associated with acceptable mortality and morbidity in selected patients with PK of colorectal origin, results in a significant extension of overall survival (OS).
Keywords: senioři; peritoneal carcinomatosis − peritoneal carcinoma index − cytoreductive surgery − hyperthermic intraperitoneal chemotherapy − HIPEC; kolorektální nádory; peritoneální nádory; Retrospective Studies; Prognosis; Colorectal Neoplasms; mužské pohlaví; cytoredukční chirurgie; míra přežití; Peritoneal Neoplasms; kombinovaná terapie; peritoneum; ženské pohlaví; prognóza; retrospektivní studie; Humans; Survival Rate; Cytoreduction Surgical Procedures; nemocnice; Peritoneum; Antineoplastic Combined Chemotherapy Protocols; Combined Modality Therapy; protokoly protinádorové kombinované chemoterapie; Hospitals; Female; Aged; lidé; Male